2022
DOI: 10.1111/jnu.12809
|View full text |Cite
|
Sign up to set email alerts
|

Professional grief among nurses in Spanish public health centers after caring for COVID‐19 patients

Abstract: Aims and objectives The aim of the present study is to investigate the professional grief suffered by nurses in various medical units, after coping with the COVID‐19 pandemic for the last 18 months. Background Addressing and acknowledging the reality of professional grief is of fundamental importance to nurses' mental health, as this condition has both professional and personal consequences. Design A qualitative, content analysis approach was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…On the other hand, we have found that those individuals presenting higher levels of stress, anxiety and depression showed higher scores on the ISDUTYP. This result is consistent with previous studies that report elevated rates of anxiety, stress and major depression [13,34,53], which may be considered risk factors for the development of bereavement syndrome. In fact, a recent study conducted in China during the COVID-19 pandemic found that health care workers reported symptoms of depression (50%) and anxiety (45%), and more speci cally that nurses who have provided direct care to COVID-19 patients have a higher risk of more severe psychological distress [35].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, we have found that those individuals presenting higher levels of stress, anxiety and depression showed higher scores on the ISDUTYP. This result is consistent with previous studies that report elevated rates of anxiety, stress and major depression [13,34,53], which may be considered risk factors for the development of bereavement syndrome. In fact, a recent study conducted in China during the COVID-19 pandemic found that health care workers reported symptoms of depression (50%) and anxiety (45%), and more speci cally that nurses who have provided direct care to COVID-19 patients have a higher risk of more severe psychological distress [35].…”
Section: Discussionsupporting
confidence: 93%
“…Professional traumatic grief symptomatology will be more accentuated in individuals who have greater stress, anxiety and depression. This hypothesis is supported by the fact that research indicates that these symptomatologies act as catalysts, exacerbating emotional and cognitive reactions linked to traumatic grief [13,34]. Similar results were found in a recent study during the COVID-19 pandemic [35].…”
supporting
confidence: 78%
See 2 more Smart Citations
“…They found that a significant number of nurses experienced professional grief, often accompanied by a range of related symptoms. Additionally, this study highlighted the importance of coping with grief, providing appropriate training and proactive support for nurses to cope with the effects of patient deaths, and changes in their work environment [15] . In this regard, Stubin CA et al reported that resilience training could improve nurses' stress levels and attention, thus leading to improved patient outcomes.…”
Section: Discussion and Resultsmentioning
confidence: 98%